Genbaku Dome VR: Experiencing Hiroshima's Atomic Legacy - Bender, Stuart; Broderick, Mick (Hiroshima International Film Festival, 2019)
This Virtual Reality experience permits users a unique view inside the World Heritage listed Genbaku Dome. This monument to the first Atomic bomb detonated over Hiroshima in August 1945 has been closed to the public since the mid-1960s. Visitors have only been able to view the exterior of the building from behind a security fence. The Genbaku Dome VR experience enables them incredibly rare access to the interior of the building. The experience comprises 3D footage intermixed with 360-degree immersive panoramas and an innovative use of archival photographs showing the aftermath of the explosion. The experience also critically engages with the legacy of Hiroshima by presenting the testimony of a 3rd generation hibakusha (A-Bomb survivor) as she experiences the interior of the monumental building for the first time. The user hears Kana reflect on her experience, juxtaposed against their own experience of/in the building, and is confronted by her ambivalence toward the encounter with this historic site.